Evaluation of Palm Oil Based Oleochemicals as Herbicide Surfactant - Mohd Shah, Zahariman (2000)
The effect of adding oleochemical-based surfactants (Agrimul PG2069, Agrimul PG2067, Sl and methyl oleate) in comparison with the organosilicone surfactant (Silwet L-77) on properties of spray solution, efficacy and uptake of glyphosate (Roundup®) for the control of P. conjugatum and D. ocimifolia was evaluated in the greenhouse. The dose-response study of glyphosate on 4-5 week old P. conjugatum and D. ocimifolia was first established. Glyphosate at 1.0 kg a.elha and above gave >90% mortality of the plants at 10 and 14 days after treatment (DAT) for P. conjugatum and D. ocimifolia, respectively. The spray deposition study showed higher amount of fluorescein deposited at these concentrations. It was estimated that glyphosate at 0.46 kg a.elha and 1.0 kg a.elha gave 50% mortality of P. conjugatum and D. ocimifolia, respectively and these rates were used in subsequent studies. Adding Agrimul PG2069 (0.025 ml/litre) and Agrimul PG2069 (0.05 ml/litre) to glyphosate spray solution gave significantly better control of P. conjugatum compared with other treatments at 10 DAT. However, methyl oleate (0.1 ml/litre) and Silwet L-77 (0.5 ml/litre) showed the highest spray deposition. On D. oCimifolia, methyl oleate at all 3 concentrations tested (0.025, 0.05 and 0.1 mll1itre) together with Silwet L-77 (0.25 ml/litre) showed significantly better efficacy compared to others at 14 DA T. The spray deposition of these surfactants was also observed to be the highest.